Shepherd’s Crook Curve: A Novel Technique for Angulated Side Branch Access in Bifurcation Angioplasty - Kanhai Lalani; M. Sudhakar Rao; Suheil Dhanse; Tom Devasia; Hashir Kareem; Ganesh Paramasivam (Methodist DeBakey Cardiovascular Journal)
Coronary intervention involving the region of bifurcation remains a challenging issue for the cardiologist as well as a complication. A number of factors including the angulation of side branch with the main branch determines the success. Though provisional strategy remains the best option in bifurcation intervention, at times a two-stent strategy cannot be avoided. We report a case in which percutaneous coronary intervention was performed on the left anterior descending artery (LAD) at its bifurcation with a major diagonal branch (> 2.5 mm). The ostium of the diagonal was diseased, and the branch took off from the LAD at an unfavorable angle (> 120°). We describe the use of the “shepherd’s crook wire curve” approach, a modification of the reverse wire technique, which allowed us to successfully wire, dilate, and protect the diagonal and so named to reflect its resemblance to the shape of a shepherd’s crook.